2021
DOI: 10.1298/ptr.e10112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rehabilitation Nutrition Care Process on Physical Function in Lung Cancer Cachexia: A Case Report

Abstract: Objectives: Patients with cancer cachexia have poor adherence to treatment, which affects their prognosis. Currently, there are many studies on the effects of rehabilitation on cancer cachexia, but there is a lack of evidence on the effects of nutrition therapy alone or in combination with rehabilitation and nutrition therapy. This article describes a case in which rehabilitation nutrition care process was effective in a patient with lung cancer who developed cancer cachexia. Methods: A 68-year-old woman was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As a result, the physical function was reported to be improved. 27 The present study was associated with several limitations. First, the database lacked detailed information, including training methods, and we were therefore unable to evaluate the recovery of the swallowing function based on the training content.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a result, the physical function was reported to be improved. 27 The present study was associated with several limitations. First, the database lacked detailed information, including training methods, and we were therefore unable to evaluate the recovery of the swallowing function based on the training content.…”
Section: Discussionmentioning
confidence: 85%
“…Shirado et al reported the effect of the rehabilitation nutrition care process in patients with lung cancer cachexia. 27 A physiotherapist prescribed resistance training, and a dietitian provided oral nutritional supplements (100 kcal, branched-chain amino acid: 3.0 g) in addition to hospital food, and adjusted the patient's energy intake to 26.96-33.05 kcal/kg/ day and protein intake to 1.07-1.14 g/kg/day as a rehabilitation nutrition care process for malnutrition, sarcopenia and cachexia. As a result, the physical function was reported to be improved.…”
Section: Discussionmentioning
confidence: 99%